From turbulence to the crisis’ diagnostics: limits and potential of sociological critique (new agenda for the European sociology) - D G Podvoyskiy; I V Trotsuk (RUDN journal of Sociology, 2013)
The article provides an overview of key issues of the last 11th Conference of the European Sociological Association “Crisis, Critique and Change” (Turin, August, 2013). The authors conduct a preliminary analysis of the concepts ‘critique’ and ‘crisis’ that quite regularly become fundamentally important and disputable in the scientific community at different stages of the history of sociological ideas. The ‘crisis-critical’ attitude is considered as one of the typical forms of sociological discourse, which has a number of specific features and is dramatically different from its ‘antipode’ — the ‘stabilization-integration’ cognitive perspective.